Isolation, identification, and pathogenicity of γ‐hemolytic Streptococcus iniae in Selenotoca multifasciata - Zi‐Chen Zhao; Ming‐Li Xiang; Jia‐Chang Zhu; Yan Wang; Gui‐Hua Li; Zhi‐Hong Zhong; Yun Sun; Heng‐Wei Deng; Wei‐Liang Guo; Yong‐Can Zhou (Journal of the World Aquaculture Society)
Abstract Streptococcus iniae is a fish pathogenic bacterium distributed worldwide. It has a wide range of hosts, strong infectivity, causes high mortality, and severely hinders the healthy development of the aquaculture industry. A fish epidemic broke out in a Selenotoca multifasciata aquaculture farm, Hainan Province, China, and resulted in numerous deaths. Sick fish showed symptoms including erratic swimming, skin darkening with generalized hemorrhages, and internal organ and brain hemorrhages. A dominant strain, SI03, isolated from the brain of a dying S. multifasciata, exhibited high virulence, and was identified as serotype I γ‐hemolytic S. iniae. Subsequently, virulence gene mRNA expression, infection kinetics, as well as the histopathology in S. multifasciata infected with SI03 were analyzed. Results showed that the mRNA expression levels of scpI, simA, pdi, pgmA, and cfi genes in γ‐hemolytic S. iniae SI03 were significantly higher than those in β‐hemolytic S. iniae ATCC 29178. These genes are associated with adhesion, invasion, and immune evasion. While the mRNA expressions of sagA‐sagI genes, which are associated with the streptolysin S, were significantly lower than those of β‐hemolytic S. iniae ATCC 29178. After being challenged with SI03, the number of bacteria in all the tested fish tissues increased significantly in 24 h. The challenged fish showed symptoms similar to those of the fish from which SI03 was originally isolated. It appears that S. iniae SI03 may have developed a compensatory pathogenic mechanism for hemolysis deficiency. This mechanism enhances its adhesion, invasion, proliferation, and immune evasion abilities. The results of this research provide a reference basis for the prevention and control of S. iniae.